2019
DOI: 10.22219/jpbi.v5i2.7219
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of medicinal plants utilized by the Baduy tribe used as a learning resource

Abstract: The existence of contextual learning resources has been known to be able to improve the meaningful learning, particularly biology learning. This research provides the information about the medicinal plant utilized by the Baduy tribe as well as its endeavour in developing the results obtained as a contextual-based module. This research and development was designed using 4D model by Thiagarajan, which was limited in three phases (define, design, and development). The data was collected using interview guideline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The loss of local knowledge in the young generation occurs in some countries including America (Vandebroek and Balick 2012), North America (Saynes-Vásquez et al 2016), Africa (Fongod et al 2014), and Brazil (Sousa et al 2012). The youth's poor traditional knowledge mainly results from an inadequate education system that fails to maintain local knowledge inherited from their ancestors (Khastini et al 2019). Preserving local knowledge can be done through documentation.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of local knowledge in the young generation occurs in some countries including America (Vandebroek and Balick 2012), North America (Saynes-Vásquez et al 2016), Africa (Fongod et al 2014), and Brazil (Sousa et al 2012). The youth's poor traditional knowledge mainly results from an inadequate education system that fails to maintain local knowledge inherited from their ancestors (Khastini et al 2019). Preserving local knowledge can be done through documentation.…”
Section: Introductionmentioning
confidence: 99%
“…Minimum inhibitory concentrations ranged from 2 mg/mL to 4 mg/mL, suggesting the use of the plant in controlling infections caused by the tested strains of Candida (C. stellatoidea). Recently, Khastini et al [54] assessed the aqueous and ethanolic extracts obtained from the maceration of Ageratum leaves for their antifungal activity, together with chemical composition screening and percentage yield calculation. Individual extracts evaluated by the disk diffusion technique were found to inhibit the C. albicans growth significantly because of the presence of various secondary metabolites in the extracts, such as flavonoids, alkaloids, tannins, steroids, and saponins and offered the same minimum inhibitory concentration (MIC) of 80 mg/mL.…”
Section: Ageratum Conyzoides Against Candida Pathogenmentioning
confidence: 99%
“…Inhibition of various fungi by diverse mechanisms also satisfies the requisite aptitude needed for the development of novel anti-resistant antifungals. Khastini et al [54] observed that aqueous and ether extracts of Ageratum leaves inhibited fungal growth by halting the formation of germ tubes by spores in the presence of the tested fungi, which is crucial for the microorganism's survival because new hyphae formation can only begin with the germ tubes. Studies substantiating the MOA of precocene II conclude that the compound exhibits its activity either by retarding fungal growth or by stopping the release of mycotoxins such as aflatoxins (B 1 , B 2 , G 1 and G 2 ) and trichothecenes.…”
Section: Mechanism Of Action (Moa)mentioning
confidence: 99%
“…The types of entomopathogens mostly found in insects are Beauveria and Metarhizium. Two kinds of mushrooms infect insects from the groups, often Lepidoptera, Homoptera, Coleoptera and Diptera (Khastini et al, 2019).…”
Section: Figure 1 Location Of the Gtg Nature Reservementioning
confidence: 99%